All the World’s a Monster - Limpár, Ildikó (Hungarian Journal of English and American Studies, 2022)
Book review:Nirta, Caterina and Andrea Pavoni, eds. Monstrous Ontologies: Politics Ethics Materiality. Series in Philosophy. Wilmington: Vernon Press, 2022. xxxiv + 220 pages. ISBN 978-1-64889-307-0. Pbk. $51.00.